2019
DOI: 10.1007/s10714-019-2589-z
|View full text |Cite
|
Sign up to set email alerts
|

Gauss–Bonnet holographic superconductors in exponential nonlinear electrodynamics

Abstract: The low-energy limits of the string theory lead to the higher-order curvature corrections for Einstein gravity. Also, they give the higher-order derivative corrections for the Maxwell or linear electrodynamics, which suggests the nonlinear electrodynamics. Inspired by this, in this paper we investigate d-dimensional holographic superconductors in the probe limit in the framework of Einstein-Gauss-Bonnet gravity and exponential nonlinear electrodynamics.Based on the Sturm-Liouville eigenvalue method, we compute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…All the studies mentioned above concerning the holographic dual models with the curvature correction are based on the Einstein-Gauss-Bonnet gravity in dimensions D ≥ 5, where we find that the higher curvature corrections make it harder for the scalar [14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] or vector [30][31][32][33][34][35][36] hair to form. As pointed out by Gregory et al in [14], one can expect this tendency to be the same even in (2 + 1)-dimensions, however, it remains obscure to what extent this suppression affects the physics of holographic superconductors in (2 + 1)dimensions.…”
Section: Jhep12(2020)192mentioning
confidence: 73%
See 1 more Smart Citation
“…All the studies mentioned above concerning the holographic dual models with the curvature correction are based on the Einstein-Gauss-Bonnet gravity in dimensions D ≥ 5, where we find that the higher curvature corrections make it harder for the scalar [14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] or vector [30][31][32][33][34][35][36] hair to form. As pointed out by Gregory et al in [14], one can expect this tendency to be the same even in (2 + 1)-dimensions, however, it remains obscure to what extent this suppression affects the physics of holographic superconductors in (2 + 1)dimensions.…”
Section: Jhep12(2020)192mentioning
confidence: 73%
“…Other generalized investigations based on the effects of the curvature correction on the holographic dual models can be found, for example, in refs. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Jhep12(2020)192mentioning
confidence: 99%
“…Figure 6 shows the plot of the Gibbs free energy vs temperature. For the values of pressure below the critical pressure Pc , the G − T diagram exhibits a swallowtail structure [57] where the Gibbs free energy of the black hole intersects with itself which is indicative of first-order phase transition between SBH and LBH (cf. Fig.…”
Section: Stability and P − V Criticallymentioning
confidence: 99%
“…The exponents α and β determine the behaviour of specific heat at constant volume [21] and behaviour of the order parameter η which is the difference between the volume of the gas phase and the volume of the liquid phase respectively. γ explains the behaviour of isothermal compressibility κ T and δ governs the behaviour of the critical isotherm P − Pc [57]. The critical exponents can be calculated by using following relations [35,36]…”
Section: Critical Exponentsmentioning
confidence: 99%
“…In this direction, lots of work studying various holographic superconductors in Einstein-Gauss-Bonnet gravity have been performed and the effects of the GB correction on the phase transition have been discovered [26][27][28][29][30][31][32][33][34][35]. Recently, Nam studied d-dimensional holographic superconductors in the probe limit in the framework of Einstein-Gauss-Bonnet gravity as well as exponential nonlinear electrodynamics, and found that the GB correction makes the formation of condensation harder, and the superconducting energy gap becomes larger when increasing GB parameter [36]. Ref.…”
Section: Introductionmentioning
confidence: 99%